NEW APPROXIMATION OF THE ENERGY SPECTRUM OF PROTON SCR - Isaeva, E. A. (Одеські астрономічні публікації, 2018)
In this paper, we consider a new approximation of the integrated energy spectrum of protons of solar cosmic rays (SCR) in the range Ep> 1-100 MeV. The sample studied contains 342 proton events for the period from 03-02-1986 to 23-07-2016. This sample is complete, since it contains very weak and superimposed proton events. The superimposed events were separated and identified according to the criteria of protonity. Out of 342 proton events, 164 events were identified and processed by the author independently. For the analysis, original records of the intensity of the proton flux with energy Ep> 1-100 MeV from the spacecraft GOES series were used. As the parameter characterizing the intensity of the proton flux, the maximum intensity of the proton flux Ip in each energy channel during the proton event was chosen. The intensity of the proton flux Ip was calculated from the preflare level. In the case of superposition of proton events, the intensity of the proton flux Ip was calculated from the level of the preceding event. Also, when processing original records of proton events, emissions associated with technical interference and with the of interplanetary shock waves were eliminated. Comparative analysis showed that all events can be conditionally divided into 5 types according to the form of the energy spectrum of protons. It is known that for most proton events, the energy spectrum of SCR protons is described quite accurately by two power-law models. However, there remains a large number of events for which the energy spectrum of protons can not be approximated accurately by two power-law models. In connection with this, another dependence was used in this work, which allows us to approximate the energy spectrum of the protons for all events quite accurately.